2006
DOI: 10.2514/1.9514
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on Specific Impulse of Partially Filled Pulse Detonation Rocket Engines

Abstract: Performance analyses of pulse detonation rocket engines (PDREs) were numerically studied, focusing on partialfill effects at ground tests. The initial detonable mixture, inert gas, fuel-fill fraction, equivalence ratio, and initial temperature of inert gas were changed as governing parameters. The simulation results were compared against those of previous studies and agreed well with them. The simulation results indicated that the initial mass fraction of the detonable mixture to total mass of the gas was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 19 publications
(17 reference statements)
0
45
0
Order By: Relevance
“…Moreover, according to Cooper et al [31] and Sato et al [32], a PDE can achieve a dramatically high specific impulse by performing a partial fill of the propellant. Numerical analysis by Morris et al [23] and an experiment by Copper et al [33] showed that the expansion effect of by nozzle became dominant, like a steady flow, if the ambient pressure around a PDE was sufficiently low.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to Cooper et al [31] and Sato et al [32], a PDE can achieve a dramatically high specific impulse by performing a partial fill of the propellant. Numerical analysis by Morris et al [23] and an experiment by Copper et al [33] showed that the expansion effect of by nozzle became dominant, like a steady flow, if the ambient pressure around a PDE was sufficiently low.…”
Section: Introductionmentioning
confidence: 99%
“…This essence of the partial fill effect is explained by considering shock impedance. 16,25) If the shock impedance of the driven gas is higher than the detonation wave, the transmitted and reflected waves are both shock waves. The reflected shock wave undergoes repeated reflection between the contact surface and the closed end wall, and the impulse increases.…”
Section: Propellant-based Specific Impulsementioning
confidence: 99%
“…In contrast, our valve can supply three different gases into a number of detonation tubes using a single rotating disk. The partial-fill effect at high operation frequencies (f set ¼ 40-160 Hz) was shown, and the elements of the driven gases in multi-pulse operation were estimated using the model proposed by Sato et al 25) The bubble model, which estimates the upper limit of the partial fill effect, 13) was applied to multi-pulse operation, and the results obtained with the model were compared with experimental results. Figure 1 shows a schematic of the rotary valve for a fourcylinder PDRE developed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to investigate the local ignitions behind shock waves under low temperature conditions, from the point of view of chemical kinetics in high-prssure (non-diluted test gases) shock tube experiments in which the non-uniformity of reflected shock waves tends to be greater because of increased viscous effects [23,24] and from the view of application systems (for example, pulse detonation engines (PDEs) [25][26][27][28][29][30][31][32][33][34][35] etc.). Therefore we focused on local ignitions induced by non-uniformity behind reflected shock waves under low-temperature conditions (Voevodsky and Soloukhin [17] : mild ignition, Gilbert and Strehlow [2] : hot spot initiation, Mayer and Oppenheim [18] : mild ignition) and investigated numerically and experimentally the local ignition position and the reason why local ignitions are located at a point distant from the reflecting wall.…”
Section: Objective Of the Present Studymentioning
confidence: 99%